Protein content of five alternate foods - Pajarillo, Flordeliza C.
SaThe protein content of five alternate foods was determined in order to evaluate their potential as protein sources. Alternate foods are defined as "non-conventional foods which can complement or substitute common protein and energy food sources available in the different provinces but not nationally eaten." The five alternate foods chosen for the study were the seeds of ipil-ipil [Leucaena leucocephala (Lam.) de Wit.], caballero [Caesalpinia pulcherrim (L.) Sw.], kapok [Ceiba pentandra (L.) Gaertn.], talisay (Terminalia catappa Linn.) and tiesa or canistel (Lucuma nervosa A. D.C.). Mature, dry samples of each seed were obtained from three different sources and were analyzed using the Kjeldahl method. The legume ipil-ipil was found to contain the highest protein level (40.29%) whilke the seed of tiesa fruit gave the lowest vale (3.97%). Kapok and talisay, which are both considered oilseeds, gave protein values of 31.1% and 22.5% respectively. Caballero, also a legume, had 23.99% protein. Based on the findings, ipil-ipil and kapok seeds can be consider good protein sources; the talisay and caballero seed moderately good protein sources the tiesa seed, a poor source of protein.